2018
DOI: 10.1002/path.5063
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the oncostatin M feed‐forward loop to suppress metastasis and therapy failure

Abstract: Deciphering the complex milieu that makes up the tumor microenvironment (TME) and the signaling engaged by TME cytokines continues to provide novel targets for therapeutic intervention. The IL-6 family member oncostatin M (OSM) has recently emerged as a potent driver of tumorigenesis, metastasis, and therapy failure, molecular programs most frequently attributed to IL-6 itself. In a recent issue of The Journal of Pathology, Kucia-Tran et al describe how elevated oncostatin M receptor (OSMR) expression results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The OSM signaling module that we identified as the downstream effect of miR551b-3p is composed of ligands (OSM and IL-31) and their receptors (OSMR and IL-31RA), and the STAT3 transcription factors are regulated through an autocrine mechanism ( Figure 7J). Emerging evidences suggest that OSM is a pivotal component in the tumor microenvironment (TME) to promote EMT and epithelial-mesenchymal plasticity (E-M plasticity) and the acquisition of CSC properties (Smigiel et al, 2018). This study has shown that the generation of cells with mesenchymal and cancer stem cell properties was unique to OSM as implicated by robust activation of two key oncogenic effector proteins STAT3 and ZEB1, which was not observed following IL-6 exposure in cancer cells.…”
Section: Discussionmentioning
confidence: 91%
“…The OSM signaling module that we identified as the downstream effect of miR551b-3p is composed of ligands (OSM and IL-31) and their receptors (OSMR and IL-31RA), and the STAT3 transcription factors are regulated through an autocrine mechanism ( Figure 7J). Emerging evidences suggest that OSM is a pivotal component in the tumor microenvironment (TME) to promote EMT and epithelial-mesenchymal plasticity (E-M plasticity) and the acquisition of CSC properties (Smigiel et al, 2018). This study has shown that the generation of cells with mesenchymal and cancer stem cell properties was unique to OSM as implicated by robust activation of two key oncogenic effector proteins STAT3 and ZEB1, which was not observed following IL-6 exposure in cancer cells.…”
Section: Discussionmentioning
confidence: 91%
“…Even if the EMP process induced by IL-6 and OSM has been shown to be reversible, there are several autocrine and paracrine positive feedback loops, leading to long-term pro-EMP signalling. In addition, both cytokines are required for the initiation and maintenance of transdifferentiated/mesenchymal and CSC-like populations, supporting a role in the acquisition of therapy resistance [ 44 , 55 , 77 , 134 , 147 , 162 , 163 ]. In conclusion, the data presented in this review, obtained from in vitro and in vivo experiments and from clinical samples, strongly supports the role of IL-6 and OSM on EMP promotion and suggests that both cytokines could be potential therapeutic targets to halt tumour progression by blocking EMP.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IL-6 activation of STAT3 functions in a positive feed-forward loop to drive the secretion of new IL-6 into the TME, which then interacts with IL-6R/gp130 to further activate JAK/STAT signaling [93,95]. OSM also potently activates a feed-forward loop, resulting in the de novo production of additional OSM and OSMR by tumor and immune cells [96]. Interestingly, OSM was first identified to play a tumor suppressive role and inhibited the proliferation of melanoma cell models [97].…”
Section: Il-6 Family Cytokine Dysregulation In the Tmementioning
confidence: 99%
“…More recently, a clinical grade OSM neutralizing antibody was used to treat pre-clinical models of squamous cell carcinoma. Again, OSM neutralizing antibodies suppressed the STAT3 feed forward signaling, resulting in reduced invasion and metastasis [96,297]. Disrupting cell surface receptor activation of STAT3 by inhibiting OSMR signaling was recently described in a study of an OSMR/gp130 antagonist (SN79), which prevents STAT3 phosphorylation in astrogliosis [298].…”
Section: Targeting Stat Activitymentioning
confidence: 99%